Strategic, administrative, and operating assistance: The value of outside consulting to pre-venture entrepreneurs - Chrisman, James J (Journal of Business Venturing, 1989)
Although there is evidence that outsiders can be a useful source of advice for pre-venture managers, few studies have examined the types of assistance they provide most effectively. Aspiring entrepreneurs need such information, however, in order to select the best outsiders for their needs. Therefore, this article investigates how pre-venture clients perceived the value of one outsider program—the Small Business Development Center—and the strategic, administrative, and operating assistance it provides. Results indicate that strategic assistance is significantly and positively associated with the perceived value of the SBDC's services and, in general, was perceived as more valuable than administrative and operating assistance. Stevenson and Sahlman (1988) contend that small companies must become more active in managing their outside advisors. To manage advisors, it is first necessary to determine the types of assistance they are best able to provide. Although previous research provides evidence that outsiders can have a positive impact on new venture performance (Chrisman et at. 1987), it has yet to be determined how outsider services can be used most effectively. In this article one source of outsider assistance—the Small Business Development Center program—is investigated to determine the types of consulting services it provides most effectively to aspiring entrepreneurs. The relationships between types of outsider assistance and clients' perceptions of their value were examined by a survey of the 249 long-term (12 contact hours or more), pre-venture clients that received counseling from one SBDC state system between July 1, 1985, and June 30, 1986. The clients were contacted in the summer of 1987 and asked to complete a questionnaire concerning the kinds of assistance they sought and the value of the service they received. Using ordinary least-squares regression analysis, the strategic, administrative, and operating assistance received were analyzed in respect to respondents'(N = 123) perceptions of the value of the services. Analysis of the pooled sample indicated that the strategic assistance provided by the SBDC was significantly and positively associated with the perceived value of its services. By contrast, neither operating nor administrative assistance was significantly associated with perceived service value. The results also provided support for the hypotheses that clients would perceive strategic assistance as more valuable than either administrative or operating assistance. In addition to the regression analysis of the pooled sample, various subsamples of respondents were also analyzed to determine if the relationships between the variables of interest were moderated by (1) the type of business clients intended to start, (2) the office where assistance was received, (3) whether consultants recommended the client proceed with the venture or not, and (4) whether the venture was subsequently started. In the main, findings for the subsamples supported the findings for the entire sample. Statistically speaking, all of the subsamples were sufficiently homogeneous to pool. However, for one group of aspiring entrepreneurs-those who received positive start-up recommendations from consultants at the SBDC's branch offices (N = 25)—the relationships between perceived service value and outsider assistance did appear to be quite different from the results for the entire sample. More specifically, there was a positive association between perceived service value and nonstrategic assistance (administrative and operating) rather than strategic assistance for these aspiring entrepreneurs. The major implication of this study is that aspiring entrepreneurs can obtain useful advice from the Small Business Development Center in formulating a new venture strategy. Clients perceived such advice as valuable and, in general, more valuable than assistance with administrative and operating problems. Aspiring entrepreneurs, therefore, may be best served by utilizing the SBDC to analyze the feasibility (including both market and financial analyses) of their proposed ventures and develop a strategic plan. Results also suggest that the value of outsider services may be moderated by the consultant, the client, and the venture. Therefore, directors of outsider assistance programs must understand the capabilities of their personnel and the needs of their clients in order to formulate an effective consulting strategy. In fact, to improve the utilization of limited resources, SBDC directors should perhaps consider adopting a strategy that focuses on what appears to be the organization's major strength: providing strategic assistance to aspiring entrepreneurs.